“DESAIN INSTRAKSIONAL : KUNCI SUKSES PEMBELAJARAN DI ERA DIGITAL” - Febry Amirullah Benny; Dirgantara Wicaksono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In today's digital era, learning has undergone a significant transformation. Instructional design plays a crucial role in creating an effective and engaging learning experience. This journal discusses instructional design concepts, the key components that influence them, as well as strategies that can be used to improve the quality of learning in a digital environment. This research aims to identify the basic principles of instructional design that can be the key to success in learning in the digital era. This study uses a qualitative approach method with literature analysis that discusses various instructional design models and their applications in the context of digital learning. The results of research in institutional design provide the key to successful learning in the digital era, namely by applying learning component components including design, process, and evaluation.